Impact of Pain Education on Pain Relief in Oncological Patients: A Narrative Review of Systematic Reviews and Meta-Analyses - Galietta, Erika; Donati, Costanza M.; Bazzocchi, Alberto; Sassi, Rebecca; Zamfir, Arina A.; Hovenier, Renee; Bos, Clemens; Hendriks, Nikki; Boomsma, Martijn F.; Huhtala, Mira; Blanco Sequeiros, Roberto; Grüll, Holger; et al. (MDPI, 2025)
Pain is a complex and burdensome symptom frequently experienced by oncological patients. Despite increased attention from healthcare providers and novel approaches, pain remains undertreated and prevalent in this patient population. Programs of patient education about pain (pain education, PE) have been proposed as a potential method to enhance pain management. However, the effectiveness of such programs and their impact on pain relief have shown variable results across studies. In this narrative review, we analyzed existing systematic reviews and meta-analyses on PE in oncological patients. A comprehensive literature search was conducted using PubMed, Scopus, and the Cochrane Library databases, following established guidelines. Studies meeting the selection criteria were selected and analyzed to evaluate the effectiveness of PE interventions. A total of nine publications, comprising six systematic reviews and three meta-analyses, were included. Across various clinical settings (inpatient and outpatient), the impact of pain education (PE) on pain intensity showed considerable variability: some reviews reported significant reductions, while others observed minimal or no effects. In contrast, PE consistently improved patients' knowledge about pain and adherence to medication. However, the available evidence did not demonstrate significant improvements in quality of life. The observed heterogeneity in the results of pain relief outcomes could be attributed to the various types of pain analyzed and the diversity of clinical settings evaluated. Furthermore, differences in study designs, comprising the inclusion of non-randomized studies, contributed to the variability in findings. It remains unclear whether the effectiveness of PE is solely attributed to the educational content or if the attention provided to patients during the intervention partly explains the effect.